Process Oriented Guided Inquiry Learning (POGIL) Model Based on Balinese Local Wisdom and Self-Efficacy towards Science Learning Outcomes - Wahyunita, I Gusti Ayu Widya Tri; Wibawa, I Made Citra; Margunayasa, I Gede (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The results of the PISA and TIMSS studies indicate low scientific literacy of students in Indonesia, particularly in elementary science Education. This study aims to analyze the effect of the Process Oriented Guided Inquiry Learning (POGIL) model based on Balinese local wisdom and self-efficacy on science learning outcomes of fifth-grade students. This study used a quasi-experimental method with a Non-Equivalent Control Group Design. The study population consisted of 188 students, with a sample of 102 students selected through a multi-stage random sampling technique. Data were collected through a self-efficacy questionnaire and a multiple-choice science learning outcome test, then analyzed using two-way ANOVA. The results showed a significant difference in science learning outcomes between the POGIL group based on Balinese local wisdom (75.55) and the conventional group (71.67). Second, there was an interaction between the POGIL model based on Balinese local wisdom and self-efficacy on science learning outcomes. Third, students with high self-efficacy had better learning outcomes with the POGIL model (79.65) compared to the conventional model (79.16). Fourth, students with low self-efficacy in the POGIL model (64.00) also had better results than the conventional group (60.21). It was concluded that the POGIL model based on Balinese local wisdom was effective in improving science learning outcomes for students with both high and low self-efficacy. Consequently, the implementation of this learning model is recommended to improve the quality of science learning in elementary schools by considering the integration of local culture and strengthening student self-efficacy.